(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper highlights the causes of the downfall of Air India that how the world’s best airline got badly spoiled. The milestones and major issues faced by Air India in Indian aviation industry are discussed. This study basically based on secondary sources of data. We used the content analysis method in this case study. Finding suggests that the main cause of the downfall of Air India is Incompetent people at the top. They couldn’t make the right decisions because they lacked knowledge and they didn’t have much experience. And neither did they have the motivation to make the right decisions. That’s why Air India story is less about the success and failures of privatization versus nationalization and more about improper management and bad decision-making. Which can be seen in a private company as well as a nationalized company. In the end, it was also discussed how this company got back to its owner (founder) again.